Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Laser pyrolysis of poly(methyl methacrylate) to high-yield and high-purity methyl methacrylate monomer: A solvent- and catalyst-free strategy for chemical recycling - Xu-Zhen Zhu; Guang-Jian He; Meng-Meng Wang; Fu-Lu Chang; Zi-Yang Hua; Hao-Bo Wang; Xuan-Qi Wu; Lun Chen (Chemical Engineering Journal, 2026)

Bioinspired orientation-regulated conductive hydrogels with hierarchical lamellar architecture for synergistic mechanical and electrical robustness - Tianhao Yu; Chao Rong; Ting Su; Shijia Wan; Bowei Zhang; Yabin Yan; Fu-Zhen Xuan (Chemical Engineering Journal, 2026)

Numerical study on the design and performance of cathode flow channels in solid oxide fuel cells based on bionic airfoil structures - Lirong Fu; Xuan Fang; Jinyi Liu; Mingwei Li (Fuel, 2026)

Experimental investigation of the gas desorption–diffusion behavior of multi-scale outburst-prone coal under constant desorption pressures - Chaojun Fan; Rui Zhu; Lei Yang; Mingkun Luo; Xiang Fu; Xuan Liu; Xiaofeng Jiang (Chemical Engineering Journal, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Nanoplastics shift arbuscular mycorrhizal fungal mediation of bacterial community assembly from diversity to compositional stability under arsenic stress - Song Liu; Xuemin Jing; Yan Wang; Maolin He; Xuan Chen; Xueli Wang; Jingwen Zhang; Qin Zeng; Xing Fan; Wei Fu; Baodong Chen; Xin Zhang; et al. (Journal of Hazardous Materials, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Constructing amorphous-crystalline FeS via coordination regulation of ethylenediamine for efficient Cr(VI) removal from groundwater - Xuan Fu; Danqing Liu; Kelin Zhang; Yuan Feng; Xiao Zhou; Qirui Guo; Yilian Li (Environmental Research, 2026)

Machine learning-enabled decoupling of strain and temperature for multifunctional sensing in soft robotic manipulation - Lulu Yang; Zhicheng Wang; Yanxun Xiang; Fu-Zhen Xuan; Yu Cang; Bin Yang (Chemical Engineering Journal, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

40Ar/39Ar geochronology, SrNd isotopes and melting conditions of the Dahongshan alkaline basalts: Constraints on mantle modification beneath the northern Yangtze Craton - Yue Song; Xuan-Ce Wang; Simon A. Wilde; Xiang-Zhong Li; Chong-Jin Pang; Si-Yu Hu; Yang Luo; Jia-Xu Tang; Si-Zhe Fu (Chemical Geology, 2026)

Interfacial microenvironment engineering of functionalized MOFs for immobilizing PET hydrolase ICCG to overcome the activity–stability trade–off in efficient PET depolymerization - Xinyu Liu; Zhong Wang; Xuan Jing; Xiaomin Hou; Si-Fu Tang (Bioresource Technology, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Elevated CO₂ promotes the translocation and degradation of strobilurin fungicides in cucumber via coupled physiological and metabolic pathways - Xuan Wu; Yangyang Fu; Xinyue Wang; Shuaipeng Lu; Shihua Zhang; Yingchao Liu; Xiaoxiao Feng (Pesticide Biochemistry and Physiology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Petrology and geochemistry of monzogranite and porphyritic granite in Laowan ore field of Qinling orogenic belt, China: Implications for gold and molybdenum mineralization - Ying-nan Chen; Cheng Xu; Wen-lei Song; Wei Fu; Ze-bang Yi; Zhi-xuan Han; Chengyu Zou; Jian-li Chen (Journal of Asian Earth Sciences, 2026)

Enhancing coalbed methane recovery with rhamnolipid: Multi-scale experimental elucidation of pore evolution and methane desorption mechanisms - Xuan Liu; Xiang Fu; Yujie Zhang; Dawei Song; Rongkun Liu (Fuel, 2026)

Investigating instability evolution of anti-dipping rock slopes under seismic dynamics: novel base-friction testing and numerical simulation - Zhihao Wu; Yang Wang; Yixin Wang; Xuan Wang; Yunyong He; Wenxi Fu (Bulletin of Engineering Geology and the Environment, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.

Climate warming and sulfide exposure jointly disrupt intestinal microbiota and barrier homeostasis in the freshwater crab Eriocheir sinensis - Yi-fu Xing; Jian Tian; Xuan-yi Zhu; Yi-fan Feng; Qi-bin Zhu; Long-long Fu; Jia-xin Yang (Aquaculture, 2026)

Dependencies of ecological drought on climatic drivers in diverse ecosystems: Implications for water resources management - Zhiwen You; Leying Fu; Huaiwei Sun; Xuan Ban; Yubo Li; Pengsheng Li; Qiming Zheng; Changqing Meng; Jie Xue; Hui Qin (Journal of Environmental Management, 2026)

Synthesis of N, S-co-doped carbon quantum dots derived from coralline algae polysaccharide and their application for grape preservation in gelatin films - Libo Wang; Xuan Fu; Kerou Gao; Yuhan Song; Hongda Zhang; Yanhui Wei; Kun Cheng (Food Bioscience, 2026)

Corrigendum to “Photophysical and chiroptical properties of a pair of chiral europium(III) enantiomers with a record external quantum efficiency” [Chem. Eng. J. 537 (2026) 176281] - Qian Xu; Jipeng Fu; Tingyu Gu; Xiaoyang Xia; Tianyi Sun; Kaina Wang; Mingxue Tang; Liang Zhou; You-Xuan Zheng (Chemical Engineering Journal, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

Differential distribution characteristics of heavy metal resistance genes and driving mechanisms of heavy metal speciation in river-lake system sediments - Yihan Chen; Yunan Sun; Yongjie Yang; Shuanggang Hu; Kangping Cui; Chao Zhu; Xian-Zhong Fu; Chen-Xuan Li; Peng Jiang; Qianli Huang (Journal of Hazardous Materials, 2026)

Integrating dynamic vegetation phenology into SWAT improves watershed nitrogen and phosphorus simulations - Zheng Wang; Jianhua Liu; Mingwei Li; Jiahao Chen; Xuan Zhang; Fanghua Hao; Yongshuo Fu (Journal of Environmental Management, 2026)

Photophysical and chiroptical properties of a pair of chiral europium(III) enantiomers with a record external quantum efficiency - Qian Xu; Jipeng Fu; Tingyu Gu; Xiaoyang Xia; Tianyi Sun; Kaina Wang; Mingxue Tang; Liang Zhou; You-Xuan Zheng (Chemical Engineering Journal, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Dynamic evolution of sex ratio in lampreys: Investigating population and ecosystem stability based on a game-theoretic framework - Zhenfen Dong; Tongtong Jiang; Tengteng Xu; Wenwen Ji; Jing Song; Yihan Gao; Yitian Zhang; Xujia Xuan; Zhifu Jia; Changhe Fu (Ecological Modelling, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Research on three-dimensional forward modeling and response characteristics for anisotropic resistivity based on multichannel electrodes - Jun-kai Yu; Fu-yu Jiang; Jiong Ni; Pei-xuan Qiao; Li-Kun Gao (Applied Geophysics, 2026)

Global impacts of dam expansion on land use and landscape pattern - Chiwei Xiao; Xuan Fu; Mingtao Xiang; Jeffrey Chiwuikem Chiaka (Resources, Conservation and Recycling, 2026)

Pore Evolution and Gas Desorption Dynamics in Lignite Enhanced by Rhamnolipid: Insights From CT 3D Reconstruction - Xuan Liu; Xiang Fu; Yujie Zhang; Dawei Song; Rongkun Liu (Rock Mechanics and Rock Engineering, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Enhanced H2O2 production via S doped N-rich biochar natural air diffusion electrode in an electro-Fenton system for efficient tetracycline degradation - Yichao Wang; Xuan Wu; Quanyou Zhao; Yujie Fu; Xijin Li; Ruidian Su; Mengchun Gao (Journal of Water Process Engineering, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Enhancing aerobic granulation for recalcitrant wastewater treatment in continuous-flow systems via zonal retrofit and cyclic alternating aeration-sludge recirculation - Xiaoqing Chen; Jiahao Liang; Jiazheng Ding; Qinghong Wang; Changgang Li; Wenyu Xie; Fu Wen; Ziwei Lv; Xuan Sun; Chunmao Chen; Dehao Li; Jing Liu (Journal of Water Process Engineering, 2026)

Interfacial electron modulation in NiCo-LDH/CoFcDCA nanohybrids enables high-performance water and urea electrolysis - Li-Wen Wang; Xuan Jing; Si-Fu Tang (Fuel, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

The effects of thermal stress on the morphology, physiological functions, gut microbiota, and metabolism of Penaeus vannamei under seawater and low-salinity conditions - Xuan-yi Zhu; Yi-fu Xing; Xiao-ting Zheng; Jian-hua Huang; Jian Qin; Jia-song Zhang (Aquaculture, 2026)

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

ISFE-Net: An important spatial feature extraction network for UAV-Based hyperspectral water quality monitoring in rivers - Jiahao Chen; Yi Xiao; Zheng Wang; Xiran Li; Xuan Zhang; Fanghua Hao; Hongtao Duan; Yongshuo Fu (Journal of Hydrology, 2026)

Self-assembled nanoparticles from sugarcane polyphenol compounds for enhanced antioxidant activity and in vivo absorption - Zhang Tong; Fang Jia-Qin; Fu Xiong; Wang Ping-Ping; Wang Chun; Fu Yu-Xuan; Chen Chun (Food Research International, 2026)

A Deep Ship Trajectory Clustering Method Based on Feature Embedded Representation Learning - Yifei Liu; Zhangsong Shi; Bing Fu; Jiankang Ke; Huihui Xu; Xuan Wang (Journal of Marine Science and Engineering, 2025)
Trajectory clustering is of great significance for identifying behavioral patterns and vessel types of non-cooperative ships. However, existing trajectory clustering methods suffer from limitations in extracting cross-spatiotemporal scale features and modeling the coupling relationship between positional and motion features, which restricts clustering performance. To address this, this study proposes a deep ship trajectory clustering method based on feature embedding representation learning (ERL-DTC). The method designs a Temporal Attention-based Multi-scale feature Aggregation Network (TA-MAN) to achieve dynamic fusion of trajectory features from micro to macro scales. A Dual-feature Self-attention Fusion Encoder (DualSFE) is employed to decouple and jointly represent the spatiotemporal position and motion features of trajectories. A two-stage optimization strategy of “pre-training and joint training” is adopted, combining contrastive loss and clustering loss to jointly constrain the embedding representation learning, ensuring it preserves trajectory similarity relationships while being adapted to the clustering task. Experiments on a public vessel trajectory dataset show that for a four-class task (K = 4), ERL-DTC improves ACC by approximately 14.1% compared to the current best deep clustering method, with NMI and ARI increasing by about 28.9% and 30.2%, respectively. It achieves the highest Silhouette Coefficient (SC) and the lowest Davies-Bouldin Index (DBI), indicating a tighter and more clearly separated cluster structure. Furthermore, its inference efficiency is improved by two orders of magnitude compared to traditional point-matching-based methods, without significantly increasing runtime due to model complexity. Ablation studies and parameter sensitivity analysis further validate the necessity of each module design and the rationality of hyperparameter settings. This research provides an efficient and robust solution for feature learning and clustering of vessel trajectories across spatiotemporal scales.

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Comparison of various machine learning algorithms for landslide susceptibility assessment: A case study of Meishan township, Zhejiang Province, China - Du Bo Wang; Fu-Wang Zhong; Xuan-Wang Zi (Applied Geophysics, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Deamination of alicyclic and aromatic amines under geologically relevant hydrothermal conditions - Yiju Liao; Alexandria Aspin; Xuan Fu; Kirtland Robinson; Ziming Yang (Organic Geochemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

In vitro assessment of dermal penetration and skin barrier impairment by per- and polyfluoroalkyl substances (PFASs) from consumer products - Xuan Zhao; Yanna Han; Mengru Fu; Shanqi Zhou; Yuhe Yang; Wenyue Zhang; Cheng Peng; Wei Zhang; Qingqing Li; Qinghe Zhu; Jie Yang (Environmental Pollution, 2025)

Novel integrated cooperative mechanism for regulating interfacial polymerization to prepare nanofiltration membrane with wrinkled structure - Xuan Wang; Tiantian Li; Minghan Su; Zehua Li; Shaofei Zhang; Yujing Zhang; Fu Liu (Desalination, 2025)

Supersaturation mechanisms and regulation strategies in nucleation-induced crystallization for high-purity fluoride recovery from photovoltaic wastewater - Zhihao Fu; Yadong Wang; Xuan Shi; Danheng Zhou; Zhilin Li; Pengkang Jin; Kunhao Li; Guohua Zhang; Ang Mei; Bingjie Sun; Yun Zhang (Chemical Engineering Journal, 2025)

Four new acylphloroglucinol glucoside derivatives from the leaves of Lysidice rhodostegia - Tian-Yuan Wu; Wei-Xuan Zheng; Xuan Zhou; Kai Zhao; Wei Wu; Li-Qin Zhan; Jin-Tao Fu; Qing Tang; Yu-Bo Zhang; Wen Li; Guo-Cai Wang (Natural Product Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

Boosting peroxymonosulfate activation by MnFe2O4/C3N5 S-scheme heterojunction for ofloxacin removal under visible-light irradiation: Performance, mechanism, and degradation pathway - Quanyou Zhao; Xuan Wu; Wenxian Fu; Siyue Huo; Yichao Wang; Mengchun Gao (Chemical Engineering Journal, 2025)

Microalgal glutaredoxin 1 interacts with transcription factor bZIP to resist cadmium stress via lipid metabolism alteration - Chao Xing; Xuan Fu; Yaru Du; Kui Liu; Hongli Yuan; Jin Liu; Jinshui Yang (Bioresource Technology, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Insight into the facet-dependent activity of MnFe2O4 in H2O2 activation for efficient oxytetracycline degradation - Quanyou Zhao; Siyue Huo; Yichao Wang; Ruidian Su; Xuan Wu; Yujie Fu; Mengchun Gao (Chemical Engineering Journal, 2025)

miR-2400 promotes proliferation of bovine skeletal muscle-derived satellite cells by regulating MAGED1 genes expression - Li Yang; Hai-Jing Luo; Zhi-An Gong; Wen-Tian Zhang; Jing-Xuan Cui; Xue-Peng Fu; Wei-Wei Zhang (Journal of Muscle Research and Cell Motility, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Optimizing zonal management framework suitable for mountain ecosystems by linking landscape, ecosystem service capacities and bundles nested - Yunqi Hao; Yihe Lü; Hui Dang; Da Lü; Chenjun Du; Yi Wang; Luning Wang; Xiaofeng Wang; Xuan Li; Bojie Fu (Journal of Environmental Management, 2025)

Construction of Pt single-atom active sites on defective Ce-MOF for enhanced photocatalytic decomposition of DMMP - Yuanyuan Yang; Xuan Jiao; Jiahao Li; Shuoying Yin; Wanbo Chen; Feiyan Fu (Journal of Environmental Chemical Engineering, 2025)

High-efficient and reversible capture of protein by oxidized and carboxymethylated starch nanocrystals: Understanding interaction mechanism and regulating complexation - Wen-Xuan Hu; Jia-Yang Fu; Liang-Sen Liao; Ping Wang; Kexin Wang; Chang-Sen Jin; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Elucidating the underlying mechanism of the bactericidal effect facilitated by a crucial flagellar protein under high-voltage electrostatic conditions - Di Pan; Pan Chu; Xiongfei Fu; Diya Wen; Hua Song; Shupei Bai; Xuan Guo (Journal of Hazardous Materials, 2025)

Ore-forming fluid for the formation of banded iron formation-hosted high-grade magnetite ores of the North China Craton: Constraints from pyrite trace elements and sulfur isotopes - Yi Wang; Li-Xing Li; Hou-Min Li; Jian-Fei Fu; Yang Dai; Xiao-Hui Wang; Xuan Wu (Journal of Asian Earth Sciences, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Human presence in the southeastern Tibetan Plateau after the Last Glacial Maximum - Jia-Jing Wang; Pei-Yang Tan; Yue Feng; Zhe-Xuan Zheng; Yu-Jie Guo; Jia-Ning He; You-Ping Wang; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Unravelling the biodegradation performance and mechanism of 3,6-dibromocarbazole by a novel strain Streptomyces sp. FW-32 - Mi Feng; Junjie Zhao; Yanqin Lu; Xuan Luo; Xinghui Feng; Yao Huang; Zijun Chen; Dongxia Fu; Jianhua Chen (Journal of Water Process Engineering, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

SERS-fluorescence dual-mode aptasensor based on hollow mesoporous silica combined with gating mechanism for the detection of aflatoxin B1 - Xuan Fu; Limei Yin; Yang Zhang; Zongbao Sun; Shanshan Xue; Heera Jayan; Hesham R. El-Seedi; Xiaobo Zou; Zhiming Guo (Food Bioscience, 2025)

Intracellular and extracellular stiffness regulation in osteosarcoma: Overcoming mechano-immune checkpoints to enhance anti-osteosarcoma immunity - Linbang Wang; Ziyu Wang; Xuan Fu; Ziqiang Yan; Jingkun Liu; Xiaoguang Liu (Chemical Engineering Journal, 2025)

Accumulation of microtubule-associated protein tau promotes hepatocellular carcinogenesis through inhibiting autophagosome-lysosome fusion - Xuemin Liu; Zhiwei Hao; Huanhuan He; Xuan Wang; Wenqi Wang; Xiji Shu; Binlian Sun; Zhiyong Hu; Shaobo Hu; Xiaoying Hou; Yue Xiao; Hongyan Zhou; et al. (Molecular and Cellular Biochemistry, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Genetic assessment of feed efficiency in the spotted Babylon Babylonia areolata - Linwei Nie; Yijie Kong; Ziyi Ma; Jingqiang Fu; Shengtai Liu; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2025)

The depletion of TFAM and p-β-catenin(S552) in mitochondria in response to BoAHV-1 productive infection leads to decreased mitochondrial biogenesis - Jiayu Lin; Xiaotian Fu; Xuan Li; Xiuyan Ding; Shitao Li; Filomena Fiorito; Liqian Zhu (Veterinary Microbiology, 2025)

Vibration reduction characteristics of steel-rubber periodic damper based on finite-domain quasi-surface wave effect - Yu-xuan Qin; Yang Tang; Zhe Zhao; Hai-chao Li; Fu-zhen Pang; Zi-teng Mao (Ocean Engineering, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Climatic driving mechanisms of the propagation from meteorological drought to agricultural and ecological droughts - Chong Li; Yongshuo Fu; Qianzuo Zhao; Xuan Zhang; Ruiqiang Ding; Fanghua Hao; Guodong Yin (Journal of Environmental Management, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Ambient-temperature α-pinene hydrogenation to cis-pinane over Ru/CeO2-H catalyst via the dimethyl-up configuration - Yu-Xuan Fu; Shu-Yi Huang; Ming-Shuai Sun; Yan Zhou; Dan-Dan Cai; Wen-Shuai Zhu; Wei Hui; Duan-Jian Tao (Chemical Engineering Journal, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Increased expression of an isoform of the long non-coding RNA, lnc37707, is associated with malathion resistance in Bactrocera dorsalis - Li-Wei Meng; Zong-Yu Luo; Fu-Qiang Zhang; Yi-Xuan Dong; Chao Ye; Wei Zhang; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2025)

Assessment of the electrocoagulation coupled with E-peroxone for ultrafiltration fouling mitigation for shale gas produced water treatment - Shi-gang Chen; Guang-dong Sun; Fan-xin Kong; Yu-Xuan Chen; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2025)

Anti-BPH lignans from Urtica triangularis subsp. pinnatifida (Hand.-Mazz.) C.J.Chen - Qing Fu; Dongliang Xiao; Nan Jiang; Dunzhu Luosang; Yangji Cidan; Yufei Xi; Hai Yan; Xinyi Zhang; Baomin Feng; Xuan Lu (Natural Product Research, 2025)

Development of a sex-specific molecular marker reveals the ZW/ZZ sex-determination system in Babylonia areolata (link 1807) - Yu Zou; Yuan Liang; Xuan Luo; Weiwei You; Minghui Shen; Jingqiang Fu; Caihuan Ke (Aquaculture, 2025)

Revealing the mobilization and age of estuarine dissolved organic matter during floods using radiocarbon and molecular fingerprints - Zhao Liang Chen; Yuanbi Yi; Ruanhong Cai; Zhe-Xuan Zhang; Wenzhao Liang; Wenjing Fu; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; et al. (Water Research, 2025)

Enhancing NH3-SCR denitrification performance through synergistic A- and B-site effects via CeFe modification of LaMnO3 - Wei Zhang; Qiao Wu; Mengyao Dong; Kang Xie; Yanshan Yin; Yunhe Zhou; Jie Li; Yehao Fu; Yaocheng Liang; Quanbin Song; Min Ruan; Shan Cheng; et al. (Fuel, 2025)

SERS aptasensor detection of aflatoxin B1 based on silicon-au-ag Janus nanocomposites - Xuan Fu; Limei Yin; Yang Zhang; Ruiyun Zhou; Hesham R. El-Seedi; Xiaobo Zou; Yunyun Gong; Zhiming Guo (Food Chemistry, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Reduction of CO2 to C2 products by tandem actives sites of a novel 2D/3D structured photoelectrocatalyst Ag/Cu2O/g-C3N4 - Hanlin Qi; Xiaoyu Han; Jiangpeng Fu; Jiayang Ma; Xuan Jia; Meichao Zhao; Xiaona Wang; Zhongtian Fu; Jun Zhang; Xin Zhao (Journal of Environmental Chemical Engineering, 2025)

A deep data fusion-based reconstruction of water index time series for intermittent rivers and ephemeral streams monitoring - Junyuan Fei; Xuan Zhang; Chong Li; Fanghua Hao; Yahui Guo; Yongshuo Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Molecular characterization of MSX2 gene and its role in regulating steroidogenesis in yak (Bos grunniens) cumulus granulosa cells - Jun Ma; Gan Yang; Xuan Qin; Luoyu Mo; Xianrong Xiong; Yan Xiong; Honghong He; Daoliang Lan; Wei Fu; Jian Li; Shi Yin (Theriogenology, 2025)

Enhanced chloramphenicol biodegradation and sustainable electricity generation via co-cultured electroactive biofilms modified with in-situ self-assembled gold nanoparticles and reduced graphene oxide - Xiao-Yu Yong; Yong-Qi Jiang; Chao Wang; Jian-Mi Wang; Huan Fu; Yu-Xuan Ji; Xin-Qi Huang; Jun Zhou; Ping Wei (Journal of Environmental Management, 2025)

Cs-Doped BCCF perovskite with enhanced surface proton acid sites for high-performance R-PCECs - Yang Gao; Kechen Liu; Xuan Zhang; Qi Li; Yinling Chang; Min Fu; Zetian Tao (Chemical Engineering Journal, 2025)

Enhancing CO2-reduction methanogenesis in microbial electrosynthesis: Role of oxygen-containing groups on carbon-based cathodes - Xuejiao Qi; Xuan Jia; Mingxiao Li; Meiying Ye; Yufang Wei; Fanhua Meng; Shanfei Fu; Beidou Xi (Bioresource Technology, 2025)

Overlooked emerging polycyclic aromatic hydrocarbons and benzofuran derivatives in soil from coking plant - Qiaofeng Ai; Lirong Gao; Jiyuan Weng; Xiaoying Cao; Yang Liu; Xin Cheng; Yingxin Zhang; Qianling Yang; Meijun Li; Jing Yang; Qiang Fu; Xuan Zheng; et al. (Science of The Total Environment, 2024)

Targeted investigation of per- and polyfluoroalkyl substances from domestic cosmetics and personal care products in China and its implications for human exposure - Xuan Zhao; Mengru Fu; Shanqi Zhou; Yanna Han; Wei Zhang; Cheng Peng; Qingqing Li; Qinghe Zhu; Jie Yang (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

A novel ternary AgBr/Ag3PO4/h-BN photocatalyst material for tetracycline degradation: Enhancement mechanism, degradation pathway and product toxicity evaluation - Xuan Jia; Xiaoyu Han; Jiangpeng Fu; Hanlin Qi; Junyan Liu; Tianfang Han; Zhongtian Fu; Binbin Wei; Xin Zhao; Feng Guo (Journal of Environmental Chemical Engineering, 2024)

Effect of different food matrices on the bioaccessibility of vitamin D3 in beverage systems: Comparison between juice and liquid milk - Shaojie Fu; Jinfeng Bi; Xiyu Jiang; Meng Liu; Xuan Liu (Food Chemistry, 2024)

Control of stepwise subduction and slab breakoff on volcanism and uplift in the Tibetan Plateau - Jian Wang; Zhi Wang; Xiugen Fu; Xuan-Ce Wang; Simon A. Wilde; Yi Fu; Jian Lin; Hengye Wei; Lijun Shen; Gang Rao; Ahmed Mansour (Earth and Planetary Science Letters, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Comprehensive analysis of benzothiazoles (BTHs), benzotriazoles (BTRs), and benzotriazole ultraviolet absorbers (BUVs) in the western South China Sea: Spatial distributions, migration tendencies and ecotoxicological relevance - Ming-Liang Zhao; Jie Fu; Xuan Ji; Jing Zhang; Zhen He; Gui-Peng Yang (Water Research, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

An integrated simulation-optimization modeling approach for coupled risk management of blue water and green water under changing environmental conditions - Yutong Li; Qian Tan; Xuan Wang; Chunhui Li; Qiang Fu (Journal of Cleaner Production, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

A novel efficient flame-retardant curing agent for epoxy resin based on P-N synergistic effect: Bio-based benzoxazine phosphate ester - Xuan Zhou; Rongzhi Li; Fei Fu; Minggui Shen; Qiaoguang Li; He Liu; Xu Xu; Zhanqian Song (Chemical Engineering Journal, 2024)

Advantages of targeted ventilation for farrowing houses: An analysis from perspectives of thermal environment, biosecurity and ventilation efficacy - Longhuan Du; Xuan Tao; Lin Zhu; Jinchuan Li; Min Fu; Jingwen Lai; Chaowu Yang; Zhiping He (Computers and Electronics in Agriculture, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Unraveling deformation mechanism of the Fukang fold-and-thrust belt: Insight into intracontinental orogenesis of the Bogda Mountain, NW China - Yu Zhen; Dengfa He; Xuan Chen; Di Li; Guobin Fu; Wenjian Guo (Marine and Petroleum Geology, 2024)

Spatiotemporal analysis of microstructure, sensory attributes, and full-spectrum metabolomes reveals the relationship between bitterness and nootkatone in Alpinia oxyphylla miquel fruit peel and seeds - Xiaolu Chen; Yong Yang; Maoyuan Wang; Qin Tian; Qian Jiang; Xuan Hu; Weiguo Ye; Wanyun Shen; Xueting Luo; Xueyan Chen; Chao Yuan; Dan Wang; et al. (Food Research International, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Partially amorphization induced S-scheme charge migration in g-C3N4/Mn1.1Fe1.9O4 defective heterojunction for boosting fenton-like degradation of tetracycline under visible light - Siyue Huo; Jingrui Deng; Quanyou Zhao; Yichao Wang; Wenxian Fu; Xuan Wu; Mengchun Gao; Haijiao Xie (Chemical Engineering Journal, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Berberine and chlorogenic acid-assembled nanoparticles for highly efficient inhibition of multidrug-resistant Staphylococcus aureus - Siyuan Fu; Xuan Yi; Yi Li; Yuanhui Li; Xiaolin Qu; Peng Miao; Yuanyuan Xu (Journal of Hazardous Materials, 2024)

Co-exposure of decabromodiphenyl ethane and cadmium increases toxicity to earthworms: Enrichment, oxidative stress, damage and molecular binding mechanisms - Zhihua Qiao; Xinlin Sun; Mengru Fu; Shanqi Zhou; Yanna Han; Xuan Zhao; Kailin Gong; Cheng Peng; Wei Zhang; Fang Liu; Chunmei Ye; Jie Yang (Journal of Hazardous Materials, 2024)

Improving maize yield estimation by assimilating UAV-based LAI into WOFOST model - Yahui Guo; Fanghua Hao; Xuan Zhang; Yuhong He; Yongshuo H. Fu (Field Crops Research, 2024)

Constructing hydroxyoxime-functionalized ionic liquid [BHIB][NTf2] for the separation of Mo(VI) from U(VI) - Feng Liu; Tao-Yuan Xiu; Wei Jin; Xuan Fu; Lin Wang; Xin-Peng Wang; Wei-Qun Shi; Li-Yong Yuan (Chemical Engineering Journal, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

The delaying effect of Clausena lansium extract on pear ring rot is related to its antifungal activity and induced disease resistance - Wen-Wu Song; Xiao-Xiang Fu; Duan-Tao Cao; Xiao-Gui Liang; Su-Ling Xiao; Min-Xuan Yuan; Ying-Jin Huang; Qing-Hong Zhou; Hong-Yi Wei; Jun-Wen Wang; Wen-Wen Peng (Postharvest Biology and Technology, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Effect of immersion time on bacterial community structure and sulfur metabolism in biofilm on concrete surface in sewer environment - Mengshu Hong; Zhaoguang Li; Xuan Shi; Qiang Fu; Shaohui Zhang; Chen Xie; Yinchu Tian; Ditao Niu (International Biodeterioration & Biodegradation, 2024)

Tanshinone IIA is superior to paricalcitol in ameliorating tubulointerstitial fibrosis through regulation of VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy - Jing-Yi Zeng; Yu Wang; Fu-Yuan Hong; Miao Miao; Yu-Ying Jiang; Zi-Xuan Qiao; Yun-Tao Wang; Xiao-Rong Bao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Glomerulosclerosis and tubulointerstitial fibrosis (TIF) are closely involved in the development of diabetic nephropathy (DN). Moreover, the development of TIF is closely related to epithelial-to-mesenchymal transition (EMT). Tanshinone IIA (Tan) has various pharmacological effects, especially the anti-fibrotic effect. And it is mainly used in the clinical treatment of cardiovascular diseases. Currently, the protective effect of Tan on DN and its possible mechanism have not been clearly elucidated. Our previous studies illustrated that Tan could improve the EMT of HK-2 cells induced by high glucose by regulating the vitamin D receptor (VDR)/Wnt/β-catenin pathway. Here, we collected demographic information and laboratory results from the National Health and Nutrition Examination Survey (NHANES) database in order to investigate the relationship between VD and DN. Then, we established a DN model and treated DN rats with Tan and paricalcitol (Par) for 6 weeks. We subsequently compared the changes in general condition, renal function, pathological changes, and TIF-related protein expression levels of control rats, DN rats induced by STZ, DN rats with Tan at 5.4 mg/kg, DN rats with Tan at 10.8 mg/kg, and DN rats with Par at 0.054 µg/kg, to explore the effect and mechanism of Tan and Par on DN rats. The results showed that VD had a protective effect against DN in diabetic patients. And we found that Tan had a protective effect on renal fibrosis in DN rats, which was superior to Par in improving the symptoms of “three more and one less,” reducing fasting blood glucose level, improving renal index, BUN/SCr, and UACR, reducing histopathological damage of kidney, and improving the expression of fibrosis-related proteins in kidney tissue by regulating VDR/Wnt/β-catenin pathway. Tan was superior to Par in ameliorating tubulointerstitial fibrosis by regulating VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy.

Simultaneous electrocoagulation and E-peroxone coupled with ultrafiltration membrane for shale gas produced water treatment - Fan-xin Kong; Yu-Xuan Chen; Yu-kun Wang; Jin-fu Chen (Chemosphere, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Hazard evaluation of forest combustibles based on the correlation between pyrolysis products and combustion parameters - Yang Yang; Teng Fu; Xuan Song; Xiu-Li Wang; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Geochemical characteristics and formation mechanism of organic-rich source rocks of mixed sedimentary strata in continental saline lacustrine basin: A case study of Permian Pingdiquan formation in the Shishugou Sag, Junggar Basin, Northwest China - Wenren Zeng; Boran Wang; Xuan Chen; Guobin Fu; Zhihuan Zhang; Zhilong Huang (International Journal of Coal Geology, 2024)

ORP-Byte: A multi-object tracking method of pigs that combines Oriented RepPoints and improved Byte - Jisheng Lu; Zhe Chen; Xuan Li; Yuhua Fu; Xiong Xiong; Xiaolei Liu; Haiyan Wang (Computers and Electronics in Agriculture, 2024)

Survival and immune responses of two populations of Babylonia areolata and their hybrids under pathogenic Vibrio challenge - Jingqiang Fu; Yuan Liang; Minghui Shen; Wengang Lü; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2024)

Episodic evolution of intracontinental orogenic deformation: Insight from the southern Bogda fold-and-thrust belt of the Tianshan Mountains, NW China - Yu Zhen; Dengfa He; Di Li; Xuan Chen; Guobin Fu (Tectonophysics, 2024)

Enhancing CH4 production in microbial electrolysis cells: Optimizing electric field via carbon cathode resistivity - Xuejiao Qi; Xuan Jia; Mingxiao Li; Wangmi Chen; Jiaqi Hou; Yufang Wei; Shanfei Fu; Beidou Xi (Science of The Total Environment, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Toxic effects of microplastics and nitrite exposure on intestinal histology, digestion, immunity, and microbial community of shrimp Litopenaeus vannamei - Yi-fu Xing; Xuan-yi Zhu; Jian-hua Huang; Yu-xiu Nan; Ya-fei Duan; Jia-song Zhang (Marine Pollution Bulletin, 2024)

Spatial compounding of droughts and hot extremes across southwest and east China resulting from energy linkages - Boying Lv; Zengchao Hao; Qian Ma; Yang Chen; Xuan Zhang; Yongshuo Fu; Fanghua Hao (Journal of Hydrology, 2024)

Late Ordovician lingulid brachiopods from the Pingliang Formation (Shaanxi Province, North China): Morphological and ecological implications - Yue Liang; Rao Fu; Yazhou Hu; Fan Liu; Baopeng Song; Mei Luo; Xinyi Ren; Jiayue Wang; Caibin Zhang; Ruisen Fang; Xuan Yang; Lars E. Holmer; et al. (Journal of Asian Earth Sciences, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

High strength, self-healing and hydrophobic fully bio-based polybenzoxazine reinforced pine oleoresin-based vitrimer and its application in carbon fiber reinforced polymers - Xuan Zhou; Minggui Shen; Fei Fu; Qiaoguang Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2024)

Spectral adjustable Re-Cs3Cu2I5 nanocrystal-in-glass composite with long-term stability - Qihua Yang; Hanqi Wei; Guihua Li; Shujuan Zhao; Yuchen Ao; Xuan Liu; Le Fu; Gemei Cai (Chemical Engineering Journal, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

ACT001 alleviates inflammation and pyroptosis through the PPAR-γ/NF-κB signaling pathway in LPS-induced alveolar macrophages - Qiang Fu; Na Shen; Tao Fang; Hewei Zhang; Yanbo Di; Xuan Liu; Chao Du; Jianshuang Guo (Genes & Genomics, 2024)

DNA-induced assembly of biocatalytic nanocompartments for sensitive and selective aptasensing of aflatoxin B1 - Xuan Xu; Junfeng Fu; Xiaotong Jiao; Yuqin Wang; Cheng Yao (Analytica Chimica Acta, 2024)

Methylseleninic acid inhibits human glioma growth in vitro and in vivo by triggering ROS-dependent oxidative damage and apoptosis - Wang Chen; Pida Hao; Qile Song; Xiaotong Feng; Xuan Zhao; Jincheng Wu; Zixiang Gong; Jinli Zhang; Xiaoyan Fu; Xianjun Wang (Metabolic Brain Disease, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Coagulation/co-catalytic membrane integrated system for fouling-resistant and efficient water purification - Yun-Jie Wang; Chen-Xuan Li; Yan Meng; Zhi-Yan Guo; Shuo Cui; Xian-Zhong Fu; Hou-Qi Liu; Wen-Qi Xia; Wen-Wei Li (Water Research, 2024)

Effects of simulated warming on soil microbial community diversity and composition across diverse ecosystems - Jiayi Zhao; Xuan Xie; Yuying Jiang; Jiaxin Li; Qi Fu; Yingbo Qiu; Xianheng Fu; Zhiyuan Yao; Zhongmin Dai; Yunpeng Qiu; Huaihai Chen (Science of The Total Environment, 2024)

Spatiotemporal variations of inter- and intra-annual extreme streamflow in the Yangtze River Basin - Anqi Huang; Guangyao Gao; Liqiang Yao; Shihua Yin; Dongfeng Li; Hong Xuan Do; Bojie Fu (Journal of Hydrology, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Construction of a floating photothermal-assisted photocatalytic system with a three-dimensional hollow porous network structure - Changyu Lu; Delu Cao; Xueying Wang; Dong Wang; Yue Xuan; Daiqiong Yang; Zhijing Fu; Yahong Zhou; Weilong Shi; Liping Wang (Chemosphere, 2024)

Phosphate activated geopolymer-based coating with high temperature resistance for sub-ambient radiative cooling - Ning Yang; Qingdong Xuan; Yang Fu; Xue Ma; Dangyuan Lei; Jianlei Niu; Jian-Guo Dai (Sustainable Cities and Society, 2024)

FinTech and sustainable financing for low carbon energy transitions: A biodiversity and natural resource perspective in BRICS economies - Li Zeng; Wing-Keung Wong; Hu Fu; Haitham A. Mahmoud; Phan The Cong; Dinh Thi Thanh Thuy; Pham Xuan Bach (Resources Policy, 2024)

Exergy, carbon footprint and cost lifecycle evaluation of cascade mechanical subcooling CO2 commercial refrigeration system in China - Baomin Dai; Yu Cao; Xuan Zhou; Shengchun Liu; Rao Fu; Cenxi Li; Dabiao Wang (Journal of Cleaner Production, 2024)

Synthesis of persistent luminescence nanocage as both drug nanocarrier and autofluorescence-free bioimaging agent for the theranostics of bacterial infection - Xuan Fu; Li-Xia Yan; Xu Zhao; Li-Jian Chen; Xiu-Ping Yan (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Characterization of simultaneous removal of nitrogen and phosphorus by novel Raoultella ornithinolytica strain YX-4 and application in real farm wastewater treatment - Weilai Fu; Youxi Zhao; Qiang Wang; Xuan Yu; Ziyang Song; Peifeng Duan; Meijuan Xu; Xian Zhang; Zhiming Rao (Bioresource Technology, 2024)

Bacterial glycerol tetraethers as a potential tool to trace marine methane cycling - Zhe‐Xuan Zhang; Jiwei Li; Hongxuan Lu; Huan Yang; Yige Zhang; Yongjie Tang; Meiyan Fu; Xiaotong Peng (Limnology and Oceanography, 2024)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial lipids that can be preserved in sedimentary archives for tens of millions of years and are ubiquitous in diverse environments, including cold seep systems. Their potential implications for detecting methane activity in deep time are, however, hampered by the multiple sources of brGDGTs in cold seeps and the lack of evidence of their stable carbon isotopes. Here, we show that brGDGTs in cold seeps are characterized by depleted stable carbon isotopic compositions of the alkyl moieties (δ 13 C = −32.9‰ to −82.7‰), indicating a methane metabolizing community origin, which is supported by the association between 16S rRNA genes and brGDGTs. We further identify unique seep‐derived brGDGT signals from the global published dataset by a tree‐based machine‐learning algorithm. This trained model, named light gradient‐boosting machine classification for paleoSEEP (GBM_SEEP), is further applied on a paleorecord across the Paleocene–Eocene Thermal Maximum (PETM), which suggests potential methane emission events during the PETM recovery phase. Collectively, our study links brGDGT production in cold seeps with methane metabolizing communities and provides a potential strategy to capture significant methane emission events using the machine‐learning model, which warrants further investigation.

Spatialized importance of key factors affecting park cooling intensity based on the park scale - Zhihua Liu; Lizhao Fu; Chaofan Wu; Zhenzhen Zhang; Zhaoyang Zhang; Xingwen Lin; Xuan Li; Yuhong Hu; Haixian Ge (Sustainable Cities and Society, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Efficient degradation of oxytetracycline by glucose modified CuFeO2 in visible-light-assisted heterogeneous activation of peroxymonosulfate system：Performance, mechanism and DFT calculation - Wenxian Fu; Siyue Huo; Minsheng Zhang; Laizhou Song; Quanyou Zhao; Xuan Wu; Mengchun Gao (Journal of Environmental Chemical Engineering, 2023)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Topsoil selenium (Se) under Se-rich farming in China: Current status, cropping impacts and ecological risk assessment - Li Qian; Ting Wang; Yajuan Shi; Qiuyun Xu; Xuan Zhou; Lingjie Ke; Ruoyu Liang; Chuancheng Fu; Xiaoqi Zheng; Guoxin Sun (Journal of Environmental Management, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Promoting photothermal catalytic CO2 reduction of Cd2In2S5/Cd0.3Zn0.7S heterojunction with encapsulated hydrogen evolution active site by accelerating charge transfer kinetics - Hongbin He; Xiangbo Zhao; Xuan Jian; Hao Zhang; Tianxu Zeng; Bingbing Feng; Yanan Hu; Zhongqiang Yuan; Xiaoming Gao; Feng Fu (Chemical Engineering Journal, 2023)

Microorganisms regulate soil phosphorus fractions in response to low nocturnal temperature by altering the abundance and composition of the pqqC gene rather than that of the phoD gene - Qingwen Shi; Qiaobo Song; Xuan Shan; Xiaoxia Li; Shuang Wang; Hongdan Fu; Zhouping Sun; Yufeng Liu; Tianlai Li (Biology and Fertility of Soils, 2023)

Aristolochic alkaloids from Piper macropodum and their anti-inflammatory activities - Chun-Yue Liu; Yong-Fu Lu; Si-Xuan Liu; Yong-Fu Li; Yan Dong; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2023)

Formation mechanism of organic-rich mixed sedimentary rocks in saline lacustrine basin, Permian Lucaogou Formation, Jimsar Sag, Junggar Basin, Northwest China - Wenren Zeng; Zhihuan Zhang; Boran Wang; Xuan Chen; Ruihui Zheng; Guobin Fu; Ying Jin (Marine and Petroleum Geology, 2023)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Multipath error mitigation method considering NLOS signal for high-precision GNSS data processing - Xuan Zou; Ruinan Fu; Jian Tang; Yawei Wang; Xiaoyun Fan; Zhiyuan Li; Chenlong Deng; Yangyang Li; Weiming Tang (GPS Solutions, 2023)

Distribution, sources, and ecological risk assessment of polycyclic aromatic hydrocarbons in sediments from Baiyang Lake, China - Liguo Fu; Yaxue Sun; Hongbo Li; Yan Chen; Hui Du; Shu-xuan Liang (Environmental Monitoring and Assessment, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

NIR responsive composite nanomaterials with in-situ deposition of cascaded nanozymes for multiple synergistic therapy of bacterial infection in diabetic mice - Yan Zhang; Chunping Wen; Yijun Liu; Anqi Li; Qiuyan Guo; Xuan Zhang; Li Fu; Shan Xu; Dan Qiao; Pengwu Zheng; Wufu Zhu; Qingshan Pan (Chemical Engineering Journal, 2023)

Biochar supported nanoscale zero-valent iron for the kinetics removal and mechanism of decabromodiphenyl ethane in the sediment - Cong Lu; Xuan Zhao; Zhihua Qiao; Kailun Luo; Shanqi Zhou; Mengru Fu; Cheng Peng; Wei Zhang (Environmental Science and Pollution Research, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Repeated exposure causes different bioaccumulation and biotoxicity of decabromodiphenyl ethane in earthworms compared to one step exposure - Mengru Fu; Xuan Zhao; Shanqi Zhou; Peng Liu; Zhihua Qiao; Yanna Han; Kailin Gong; Cheng Peng; Wei Zhang; Jinhong Wu (Process Safety and Environmental Protection, 2023)

Complete genome sequence of Bacillus cereus 2-6A, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Pacific Ocean - Xuan Zou; Chuan-Lei Suo; Xiao-Mei Geng; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Peng Wang; Mei-Ling Sun (Marine Genomics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Correction to: Technical characteristics and coating formation mechanism of gilded silver products unearthed from the Consort Tomb of Emperor Shengzong of the Liao dynasty - Yanbing Shao; Xuan Lu; Wenbin Fu; Fengrui Jiang; Junchang Yang; Zhiyong Gai; Limin Dong (Archaeological and Anthropological Sciences, 2023)

Technical characteristics and coating formation mechanism of gilded silver products unearthed from the Consort Tomb of Emperor Shengzong of the Liao dynasty - Yanbing Shao; Xuan Lu; Wenbin Fu; Fengrui Jiang; Junchang Yang; Zhiyong Gai; Limin Dong (Archaeological and Anthropological Sciences, 2023)
Compared with other gold plating processes, mercury gilding was widely used in ancient China due to the less consumption of gold and excellent adhesion between the gold layer and substrate. Herein, the comprehensive analyses of the silver crown and boots unearthed from the Consort Tombs of Emperor Shengzong (圣宗萧贵妃) of the Liao (辽) Dynasty reveal the surface composition and structural characteristics and also the unique multilayered structure and cross-sectional compositional distribution of the gold layer. First, the existence of mercury on the golden surface of cultural relics, as well as the unique porous structure and granular surface morphology, indicate that the artifacts were probably processed using mercury gilding. In addition, the intermetallic compound, i.e., Au 5 Hg, in the gold layer indicates that the processing temperature was 388–419 ℃; thus, the formation mechanism was the transformation of solid solution in the amalgam to intermetallic compound during the heating of Au-Hg system. Moreover, the cross-sectional transition layer is mainly composed of Ag and Hg due to the interstitial diffusion of mercury atoms at room temperature and vacancy diffusion of silver atoms during the heating process, bonding the gold layer with the substrate. Obviously, the bonding mechanism of the gold layer and substrate was interstitial diffusion and vacancy diffusion within the Ag-Hg system. The current work reveals the special multilayered cross-section of silver gilding relics and shows that mercury played a crucial role in both the formation of the gold layer and bonding between the gold layer and substrate during the silver gilding process.

Global warming is increasing the discrepancy between green (actual) and thermal (potential) seasons of temperate trees - Yongshuo H. Fu; Xiaojun Geng; Shouzhi Chen; Hao Wu; Fanghua Hao; Xuan Zhang; Zhaofei Wu; Jing Zhang; Jing Tang; Yann Vitasse; Constantin M. Zohner; Ivan Janssens; et al. (Global Change Biology, 2023)
Over the past decades, global warming has led to a lengthening of the time window during which temperatures remain favorable for carbon assimilation and tree growth, resulting in a lengthening of the green season. The extent to which forest green seasons have tracked the lengthening of this favorable period under climate warming, however, has not been quantified to date. Here, we used remote sensing data and long‐term ground observations of leaf‐out and coloration for six dominant species of European trees at 1773 sites, for a total of 6060 species–site combinations, during 1980–2016 and found that actual green season extensions (GS: 3.1 ± 0.1 day decade −1 ) lag four times behind extensions of the potential thermal season (TS: 12.6 ± 0.1 day decade −1 ). Similar but less pronounced differences were obtained using satellite‐derived vegetation phenology observations, that is, a lengthening of 4.4 ± 0.13 and 7.5 ± 0.13 day decade −1 for GS and TS, respectively. This difference was mainly driven by the larger advance in the onset of the thermal season compared to the actual advance of leaf‐out dates (spring mismatch: 7.2 ± 0.1 day decade −1 ), but to a less extent caused by a phenological mismatch between GS and TS in autumn (2.4 ± 0.1 day decade −1 ). Our results showed that forest trees do not linearly track the new thermal window extension, indicating more complex interactions between winter and spring temperatures and photoperiod and a justification of demonstrating that using more sophisticated models that include the influence of chilling and photoperiod is needed to accurately predict spring phenological changes under warmer climate. They urge caution if such mechanisms are omitted to predict, for example, how vegetative health and growth, species distribution and crop yields will change in the future.

Remediation of lindane contaminated soil by fluidization-like dielectric barrier discharge - Shuo Zhang; Zhen Liu; Shuran Li; Shihao Zhang; Hui Fu; Xuan Tu; Wenyi Xu; Xing Shen; Keping Yan; Ping Gan; Xiujuan Feng (Journal of Hazardous Materials, 2023)

Humidity sensing based strategy for in situ probing and manipulating electrified interfacial water adsorption dynamics - Tianshu Chu; Xinyuan Mao; Bowei Zhang; Fu-Zhen Xuan (Chemical Engineering Journal, 2023)

Antihypertensive effect of fucoidan from Yangqicai (Sargassum fusiforme) in EA.hy-926 cells and spontaneously hypertensive rats - FangTong Li; Xue Li; YunHua Fu; Xuan Hu; DongYue Zhou; YuLin Dai; YouJin Jeon (Journal of Applied Phycology, 2023)

Synthesis of bifunctional NiFe layered double hydroxides (LDH)/Mo-doped g-C3N4 electrocatalyst for efficient methanol oxidation and seawater splitting - Yufei Du; Yichu Zhang; Xunchi Pu; Xiaoying Fu; Xuan Li; Linqin Bai; Yongjun Chen; Jin Qian (Chemosphere, 2023)

Informing the SWAT model with remote sensing detected vegetation phenology for improved modeling of ecohydrological processes - Shouzhi Chen; Yongshuo H. Fu; Zhaofei Wu; Fanghua Hao; Zengchao Hao; Yahui Guo; Xiaojun Geng; Xiaoyan Li; Xuan Zhang; Jing Tang; Vijay P. Singh; Xuesong Zhang (Journal of Hydrology, 2023)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

iTRAQ-based proteomics analysis of diethylstilbestrol induced dysfunction of testicular gubernaculum development in mouse - Hongyan Ping; Degang Wang; Maxian Fu; Kaihong Chen; Jiuhong Zhang; Ke Li; Xuewu Jiang; Shouxing Duan; Xuan Zhang (Molecular & Cellular Toxicology, 2022)

Goethite and lepidocrocite catalyzing different double-oxidant systems to degrade chlorophenol - Dan Zhong; Weinan Feng; Wencheng Ma; Xinyue Liu; Jun Ma; Ziyi Zhou; Xuan Du; Fu He (Environmental Science and Pollution Research, 2022)

Cordycepin enhances hyperthermia-induced apoptosis and cell cycle arrest by modulating the MAPK pathway in human lymphoma U937 cells - Liying Shi; He Cao; Siyu Fu; Zixian Jia; Xuan Lu; Zhengguo Cui; Dayong Yu (Molecular Biology Reports, 2022)

Correction to: Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Accurate detection method of high-density polyethylene film leakage location based on secondary electric potential difference - Fu-Yu Jiang; Pei-Xuan Qiao; Li-Kun Gao; Hai-Jun Chen (Applied Geophysics, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Extracellular vesicles derived from human bone marrow mesenchymal stem cells protect rats against acute myocardial infarction-induced heart failure - Liying Xuan; Danni Fu; Dong Zhen; Chengxi Wei; Dongsong Bai; Lijun Yu; Guohua Gong (Cell and Tissue Research, 2022)

Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Higher temperature sensitivity of flowering than leaf‐out alters the time between phenophases across temperate tree species - Xiaojun Geng; Yongshuo H. Fu; Shilong Piao; Fanghua Hao; Hans J. De Boeck; Xuan Zhang; Shouzhi Chen; Yahui Guo; Janet S. Prevéy; Yann Vitasse; Josep Peñuelas; Ivan A. Janssens; et al. (Global Ecology and Biogeography, 2022)
Aim The aims of this study were to evaluate the changes in the length of the time period between leaf‐out and flowering across temperate tree species, and associate these changes with potential physiological and environmental drivers to enhance mechanistic insight into these phenomena. Location Central Europe. Time period 1980–2016. Major taxa studied Six temperate woody species. Methods Statistical analyses were carried out based on long‐term ground observations of both spring leaf‐out and flowering across temperate tree species during 1980–2016, a period characterized by rapid warming. Results The temperature sensitivity of flowering (−5.4 ± 0.04 days/℃, mean ± SE ) was higher than that of leaf‐out (−4.6 ± 0.04 days/℃) across all species, regardless of whether leaf‐out occurred before or after flowering. This study postulates a hypothesis attributing the different temperature sensitivities to different thermal sensitivities, thermal requirements, and photoperiodic controls. Main conclusions The larger temperature sensitivity of flowering than leaf‐out resulted in an extended time period between flowering and leaf‐out in species that bloom before leafing out, but a shorter time period between these phenophases in species with the opposite strategy. We would like to emphasize the importance of changes in time period between different phenophases, and we recommend conducting experimental research to reveal the underlying mechanisms of plant phenology response to climate change, and to explore its potential ecological implications.

Overexpression of a putative 12-oxophytodienoate reductase gene, EpOPR1, enhances acetylshikonin production in Echium plantagineum - Jiangyan Fu; Ran Ren; Suo Jin; Rongjun Fang; Zhongling Wen; Minkai Yang; Xuan Wang; Bao Liu; Tongming Yin; Guihua Lu; Yonghua Yang; Jinliang Qi (In Vitro Cellular & Developmental Biology - Plant, 2022)

Adsorption Removal of Phosphate and Fluoride from Aqueous Solution Using Oily Sludge-based Pyrolysis Residue - Huifen Yang; Peng Fu; Ge Zhang; Qingping Zhang; Xuan Li (Environmental Processes, 2021)

Deciphering the rhizobacterial assemblages under the influence of genetically engineered maize carrying mcry genes - Aliya Fazal; Zhongling Wen; Minkai Yang; Yonghui Liao; Jiangyan Fu; Cong He; Xuan Wang; Wencai Jie; Farman Ali; Dongqing Hu; Tongming Yin; Zhi Hong; et al. (Environmental Science and Pollution Research, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Devosia sediminis sp. nov., isolated from subterranean sediment - Fu Ma; Zhi-Da Zi; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2021)

Multi-element Characteristics of Chinese Medical Baishao (Paeoniae Radix Alba) and Their Decoctions - Xuan Xue; Guijian Liu; Yong Wei; Biao Fu; Feng Li; Delin Wu; Wei Zhang (Biological Trace Element Research, 2021)

Expansion law and influence factors of hydraulic fracture under the influence of coal pillar - Binwei Xia; Changnan Ou; Xuan Zhang; Yuanhao Fu (Arabian Journal of Geosciences, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Cloning and functional analysis of EpGHQH1 in shikonin production of Echium plantagineum - Jiangyan Fu; Guihua Lu; Minkai Yang; Hua Zhao; Wencai Jie; Aliya Fazal; Xuan Wang; Zhongling Wen; Rongjun Fang; Bao Liu; Tongming Yin; Jinliang Qi; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Decreasing control of precipitation on grassland spring phenology in temperate China - Yongshuo H. Fu; Xuancheng Zhou; Xinxi Li; Yaru Zhang; Xiaojun Geng; Fanghua Hao; Xuan Zhang; Heikki Hanninen; Yahui Guo; Hans J. De Boeck (Global Ecology and Biogeography, 2021)
Aim Vegetation phenology is highly sensitive to climate change. The timing of spring phenology in temperate grasslands is regulated primarily by temperature and precipitation. The aim of this study was to determine whether the primary factor regulating vegetation phenology has changed under ongoing climate change and the underlying mechanisms. Location Temperate semi‐dry grasslands in China. Time period 1982–2015. Major taxa studied Temperate grassland. Methods We extracted start of season (SOS) dates using five standard methods from satellite‐derived normalized difference vegetation index (NDVI) data and determined the primary factor regulating spring phenology using partial correlation analysis. Results The SOS date did not change significantly during the entire 1982–2015 study period in these semi‐dry grasslands, but interannual variability increased significantly from the first subperiod [1982–1998, 8.8 ± 1.1 days (mean ± SE )] to the second subperiod (1999–2015, 10.3 ± 1.1 days). Interestingly, we found that the primary factor regulating SOS shifted from precipitation during 1982–1998 to temperature during 1999–2015. Specifically, we found that during the first period, the SOS in 67.5% of the study area was determined by precipitation (mean partial correlation coefficient, r = 0.58 ± 0.16), but during the second period the main regulating factor in 75.0% of the study area was temperature ( r = 0.61 ± 0.14). Main conclusions The change in the primary driver of spring phenology was attributed mainly to significant increases in preseason precipitation. Our study highlights that the response of spring phenology to climatic factors might change under ongoing climate change. This shift should be addressed in phenology models to simulate grassland phenology better, in addition to its impact on carbon and water cycles in future climate conditions.

Climate warming increases spring phenological differences among temperate trees - Xiaojun Geng; Yongshuo H. Fu; Fanghua Hao; Xuancheng Zhou; Xuan Zhang; Guodong Yin; Yann Vitasse; Shilong Piao; Kechang Niu; Hans J. De Boeck; Annette Menzel; Josep Peñuelas (Global Change Biology, 2020)
Climate warming has substantially advanced spring leaf flushing, but winter chilling and photoperiod co‐determine the leaf flushing process in ways that vary among species. As a result, the interspecific differences in spring phenology (IDSP) are expected to change with climate warming, which may, in turn, induce negative or positive ecological consequences. However, the temporal change of IDSP at large spatiotemporal scales remains unclear. In this study, we analyzed long‐term in‐situ observations (1951–2016) of six, coexisting temperate tree species from 305 sites across Central Europe and found that phenological ranking did not change when comparing the rapidly warming period 1984–2016 to the marginally warming period 1951–1983. However, the advance of leaf flushing was significantly larger in early‐flushing species EFS (6.7 ± 0.3 days) than in late‐flushing species LFS (5.9 ± 0.2 days) between the two periods, indicating extended IDSP. This IDSP extension could not be explained by differences in temperature sensitivity between EFS and LFS; however, climatic warming‐induced heat accumulation effects on leaf flushing, which were linked to a greater heat requirement and higher photoperiod sensitivity in LFS, drove the shifts in IDSP. Continued climate warming is expected to further extend IDSP across temperate trees, with associated implications for ecosystem function.

Experimentally Induced Sepsis Causes Extensive Hypomyelination in the Prefrontal Cortex and Hippocampus in Neonatal Rats - Peixian Huang; Xuan Chen; Xiaoli Hu; Qiuping Zhou; Lanfen Lin; Shuqi Jiang; Hui Fu; Yajie Xiong; Hongke Zeng; Ming Fang; Chunbo Chen; Yiyu Deng (NeuroMolecular Medicine, 2020)

Temporal and Spatial Dynamics of Astroglial Reaction and Immune Response in Cuprizone-Induced Demyelination - Jun An; Jun-Jun Yin; Yan He; Ruo-Xuan Sui; Qiang Miao; Qing Wang; Jie-Zhong Yu; Jing-Wen Yu; Fu-Dong Shi; Cun-Gen Ma; Bao-Guo Xiao (Neurotoxicity Research, 2020)

Inhibition of chemotherapy-related breast tumor EMT by application of redox-sensitive siRNA delivery system CSO-ss-SA/siRNA along with doxorubicin treatment - Xuan Liu; Xue-qing Zhou; Xu-wei Shang; Li Wang; Yi Li; Hong Yuan; Fu-qiang Hu (Journal of Zhejiang University-SCIENCE B, 2020)

Developmental basis for flower sex determination and effects of cytokinin on sex determination in Plukenetia volubilis (Euphorbiaceae) - Yan Luo; Bang-Zhen Pan; Lu Li; Chen-Xuan Yang; Zeng-Fu Xu (Plant Reproduction, 2020)
Key message Cytokinin might be an important factor to regulate floral sex at the very early stage of flower development in sacha inchi. Abstract Sacha inchi ( Plukenetia volubilis , Euphorbiaceae) is characterized by having female and male flowers in a thyrse with particular differences. The mechanisms involved in the development of unisexual flowers are very poorly understood. In this study, the inflorescence and flower development of P. volubilis were investigated using light microscopy and scanning electron microscopy. We also investigated the effects of cytokinin on flower sex determination by exogenous application of 6-benzyladenine (BA) in P. volubilis . The floral development of P. volubilis was divided into eight stages, and the first morphological divergence between the male and female flowers was found to occur at stage 3. Both female and male flowers can be structurally distinguished by differences in the shape and size of the flower apex after sepal primordia initiation. There are no traces of gynoecia in male flowers or of androecia in female flowers. Exogenous application of BA effectively induced gynoecium primordia initiation and female flower development, especially at the early flower developmental stages. We propose that flower sex is determined earlier and probably occurs before flower initiation, either prior to or at inflorescence development due to the difference in the position of the female and male primordia in the inflorescence and in the time of the female and male primordia being initiated. The influence of cytokinin on female primordia during flower development in P. volubilis strongly suggests a feminization role for cytokinin in sex determination. These results indicate that cytokinin could modify the fate of the apical meristem of male flower and promote the formation of carpel primordia in P. volubilis.

Induced cell proliferation in pearl oyster - Wenjuan Li; Jiamin Liu; Xingrong Xuan; Qian Li; Zhiyi Shi; Ye Zhang; Zhiyi Bai; Yuanshuai Fu (Aquaculture International, 2020)

Shortened temperature‐relevant period of spring leaf‐out in temperate‐zone trees - Yongshuo H. Fu; Xiaojun Geng; Fanghua Hao; Yann Vitasse; Constantin M. Zohner; Xuan Zhang; Xuancheng Zhou; Guodong Yin; Josep Peñuelas; Shilong Piao; Ivan A. Janssens (Global Change Biology, 2019)
Temperature during a particular period prior to spring leaf‐out, the temperature‐relevant period (TRP), is a strong determinant of the leaf‐out date in temperate‐zone trees. Climatic warming has substantially advanced leaf‐out dates in temperate biomes worldwide, but its effect on the beginning and length of the TRP has not yet been explored, despite its direct relevance for phenology modeling. Using 1,551 species–site combinations of long‐term (1951–2016) in situ observations on six tree species (namely, Aesculus hippocastanum , Alnus glutinosa , Betula pendula , Fagus sylvatica , Fraxinus excelsior , and Quercus robur ) in central Europe, we found that the advancing leaf‐out was accompanied by a shortening of the TRP. On average across all species and sites, the length of the TRP significantly decreased by 23% ( p

Photoelectrocatalytic degradation of atrazine by boron-fluorine co-doped TiO2 nanotube arrays - He-xuan Wang; Li-nan Zhu; Fu-qiao Guo (Environmental Science and Pollution Research, 2019)

Comparative genomic analysis unravels the transmission pattern and intra-species divergence of acute hepatopancreatic necrosis disease (AHPND)-causing Vibrio parahaemolyticus strains - Qian Yang; Xuan Dong; Guosi Xie; Songzhe Fu; Peizhuo Zou; Jing Sun; Yi Wang; Jie Huang (Molecular Genetics and Genomics, 2019)

Daylength helps temperate deciduous trees to leaf‐out at the optimal time - Yongshuo H. Fu; Xuan Zhang; Shilong Piao; Fanghua Hao; Xiaojun Geng; Yann Vitasse; Constantin Zohner; Josep Peñuelas; Ivan A. Janssens (Global Change Biology, 2019)
Global warming has led to substantially earlier spring leaf‐out in temperate‐zone deciduous trees. The interactive effects of temperature and daylength underlying this warming response remain unclear. However, they need to be accurately represented by earth system models to improve projections of the carbon and energy balances of temperate forests and the associated feedbacks to the Earth's climate system. We studied the control of leaf‐out by daylength and temperature using data from six tree species across 2,377 European phenological network ( www.pep725.eu ), each with at least 30 years of observations. We found that, in addition to and independent of the known effect of chilling, daylength correlates negatively with the heat requirement for leaf‐out in all studied species. In warm springs when leaf‐out is early, days are short and the heat requirement is higher than in an average spring, which mitigates the warming‐induced advancement of leaf‐out and protects the tree against precocious leaf‐out and the associated risks of late frosts. In contrast, longer‐than‐average daylength (in cold springs when leaf‐out is late) reduces the heat requirement for leaf‐out, ensuring that trees do not leaf‐out too late and miss out on large amounts of solar energy. These results provide the first large‐scale empirical evidence of a widespread daylength effect on the temperature sensitivity of leaf‐out phenology in temperate deciduous trees.

Prediction of mizoribine pharmacokinetic parameters by serum creatinine in renal transplant recipients - Pan Chen; Xuan Xu; Longshan Liu; Jingjing Wu; Jingjie Li; Qian Fu; Jie Chen; Changxi Wang (European Journal of Clinical Pharmacology, 2019)

Preliminary investigation of ixodid ticks in Jiangxi Province of Eastern China - Weiqing Zheng; Xuenan Xuan; Renlong Fu; Huiying Tao; Rongman Xu; Yangqing Liu; Xiaoqing Liu; Jiafu Jiang; Haixia Wu; Hongmei Ma; Yi Sun; Haiying Chen (Experimental and Applied Acarology, 2019)

A novel method for predicting cadmium concentration in rice grain using genetic algorithm and back-propagation neural network based on soil properties - Yi Xuan Hou; Hua Fu Zhao; Zhuo Zhang; Ke Ning Wu (Environmental Science and Pollution Research, 2018)

The isolation of the IGT family genes in Malus × domestica and their expressions in four idiotype apple cultivars - Limin Wang; Wenbo Cai; Chuanhui Du; Yan Fu; Xuan Xie; Yuandi Zhu (Tree Genetics & Genomes, 2018)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

Plantar blood flow response to accumulated pressure stimulus in diabetic people with different peak plantar pressure: a non-randomized clinical trial - Fang Pu; Weiyan Ren; Hongyuan Fu; Xuan Zheng; Min Yang; Yih-Kuen Jan; Yubo Fan (Medical & Biological Engineering & Computing, 2018)

Transferability of Conceptual Hydrological Models Across Temporal Resolutions: Approach and Application - Meng-Xuan Jie; Hua Chen; Chong-Yu Xu; Qiang Zeng; Jie Chen; Jong-Suk Kim; Sheng-lian Guo; Fu-Qiang Guo (Water Resources Management, 2018)

Long-term plastic film mulching and fertilization treatments changed the annual distribution of residual maize straw C in soil aggregates under field conditions: characterization by 13C tracing - Xinxin Jin; Tingting An; Aaron R. Gall; Shuangyi Li; Liangjie Sun; Jiubo Pei; Xiaodan Gao; Xuan He; Shifeng Fu; Xueli Ding; Jingkuan Wang (Journal of Soils and Sediments, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Increasing winter conductive heat transfer in the Arctic sea-ice-covered areas: 1979–2014 - Xieyu Fan; Haibo Bi; Yunhe Wang; Min Fu; Xuan Zhou; Xiuli Xu; Haijun Huang (Journal of Ocean University of China, 2017)

An analysis of patents for anesthetic laryngoscopes - Cheng-dong Ji; Xin Pan; Yuan-chang Xiong; Xuan Guo; Shu-wen Qian; Chang Xu; Qiang-qiang Fu; Zhi-ping Yang; Yu Ma; Yue-zhu Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Serum uric acid levels in patients with infections of central nervous system - Jia Liu; Min Li; Xuan Wang; Huan Yi; Li Xu; Xiu-feng Zhong; Fu-hua Peng (Acta Neurologica Belgica, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Retraction Note to: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Complex seismic wavefield interpolation based on the Bregman iteration method in the sparse transform domain - Fu-Yan Gou; Cai Liu; Yang Liu; Xuan Feng; Fang-Zi Cui (Applied Geophysics, 2014)

RETRACTED ARTICLE: Genetic polymorphisms in VDR, ESR1 and ESR2 genes may contribute to susceptibility to Parkinson’s disease: a meta-analysis - Zhan Gao; Hong-Juan Fu; Ju-Jun Xue; Zhi-Xuan Wu; Li-Bo Zhao (Molecular Biology Reports, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Induced pluripotent stem cell-related genes influence biological behavior and 5-fluorouracil sensitivity of colorectal cancer cells - Zhong Shi; Rui Bai; Zhi-xuan Fu; Yong-liang Zhu; Rong-fu Wang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Linkage with cathepsin B-sensitive dipeptide promotes the in vitro and in vivo anticancer activity of PEGylated tumor necrosis factor-alpha (TNF-α) against murine fibrosarcoma - ChuanYun Dai; Ya Fu; Biao Li; YiGuang Wang; Xuan Zhang; JianCheng Wang; Qiang Zhang (Science China Life Sciences, 2011)

Osteogenic role of endosomal chloride channels in MC3T3-E1 cells - Huan Wang; Na Huo; Feifei Li; Shanmin Fu; Yang Xue; Ting Yang; Xuan Wen; Yin Ding; Xiaohong Duan (Molecular and Cellular Biochemistry, 2010)

Population variation of invasive Spartina alterniflora can differentiate bacterial diversity in its rhizosphere - Ming Nie; Le Xuan Gao; Jun Hong Yan; Xiao Hua Fu; Ming Xiao; Ji Yang; Bo Li (Plant Ecology, 2010)

Removal of Cu2+ and dye from wastewater using the heavy metal precipitant N,N-bis-(dithiocarboxy)piperazine - F. L. Fu; Q. R. Xuan; R. M. Chen; Y. Xiong (Environmental Chemistry Letters, 2006)

Relationship between resort life cycle and residents’ perception and attitude - Xiao-zhong Yang; Lin Lu; Guang-sheng Zhang; Song Lu; Guo-fu Xuan (Chinese Geographical Science, 2004)